Bureaucratic pluralism in global development: challenges for Germany and the United States - Erik Lundsgaarde (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
A variety of governmental actors within OECD-DAC donor countries oversee funding distributed to developing countries. This paper examines the role of diverse bureaucracies within the development policy systems of Germany and the United States and highlights core questions that their international engagement presents for the future of development cooperation. The paper reviews trends in funding across bureaucracies over the last decade, provides an overview of existing mechanisms for enhancing cross-governmental consistency and analyses proposals to reform the organisational set-up of the two systems. Although the challenges presented by sector-specific bureaucracies vary across donor contexts and within particular sectors of engagement, their presence in the cooperation landscape clearly creates pressure on foreign affairs and development bureaucracies to redefine their roles in the management of international cooperation. In preparing for future challenges, these bureaucratic actors will need to clearly articulate their own geographical, thematic and coordination competences in order to determine how the expertise and other resources from varied governmental actors can be effectively combined.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik